HSF1 Protects Neurons through a Novel Trimerization- and HSP-Independent Mechanism - Verma, Pragya; Pfister, Jason A.; Mallick, Sathi; D'Mello, Santosh R. (The Journal of neuroscience, 2014)
Heat shock factor 1 (HSF1) protects neurons from death caused by the accumulation of misfolded proteins. It is believed that this protective effect is mediated by the transcriptional stimulation of genes encoding heat shock proteins (HSPs), a family of chaperones that refold or degrade misfolded proteins. Whether HSF1 is protective when neuronal death is not caused by protein misfolding has not been studied. Here, we report that HSF1 expression is necessary for the survival of rat neurons and that HSF1 mRNA and protein expression is reduced in neurons primed to die. Knock-down of HSF1 induces death of otherwise healthy neurons, whereas reestablishment of elevated levels of HSF1 protects neurons even when death is not due to accumulation of misfolded proteins. Neuroprotection by HSF1 does not require its trimerization, an event obligatory for the binding of HSF1 to heat shock elements within HSP gene promoters. Moreover, knock-down of HSP70 or blockade of HSP90 signaling does not reduce neuroprotection by HSF1. Although several neuroprotective molecules and signaling pathways, including CaMK, PKA, Casein kinase-II, and the Raf-MEK-ERK and PI-3K-Akt pathways, are not required for HSF1-mediated neuroprotection, protection is abrogated by inhibition of classical histone deacetylases (HDACs). We report that the novel mechanism of neuroprotection by HSF1 involves cooperation with SIRT1, an HDAC with well documented neuroprotective effects. Using a cell culture model of Huntington's disease, we show that HSF1 trimerization is not required for protection against mutant huntingtin-induced neurotoxicity, suggesting that HSF1 can protect neurons against both proteinopathic and nonproteinopathic death through a noncanonical pathway.